Efficient bilateral trade with interdependent values: The use of two-stage mechanisms - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2025)
Efficient, voluntary bilateral trades are generally not implementable in an interdependent values environment where agents’ information is ex ante symmetric (i.e., both parties have private information, and each party’s valuation depends on the other’s information in the same way). To address this limitation, we propose two-stage mechanisms in which (i) the outcome (e.g., allocation of goods) is determined first, (ii) agents partially learn the state via their own outcome-decision payoffs, and (iii) transfers are finally made. We introduce the approximate shoot-the-liar (AS) mechanism and the generalized shoot-the-liar (GS) mechanism and identify mild conditions for each mechanism to achieve the desired properties. The AS mechanism ensures “approximately” efficient, voluntary trades. Additionally, we establish that if fully efficient, voluntary trades are required, there is no loss of generality in focusing on the GS mechanism. Finally, we identify a necessary and sufficient condition for the GS mechanism to implement efficient, voluntary trades.